2024
DOI: 10.5477/cis/reis.159.13
|View full text |Cite
|
Sign up to set email alerts
|

¿Hacia un nuevo modelo de paternidad? Discursos sobre el proceso de implicación paterna en la España urbana

Abstract: Análisis del discurso • Cuidado de los hijos • Género • Relaciones padreshijos • Sociología de la familia ResumenEn las últimas décadas los estudios cuantitativos han demostrado un aumento en la implicación paterna. Estos cambios han supuesto la emergencia de la hipótesis de un nuevo modelo de padre. El objetivo de este trabajo es el de explorar los discursos de los padres españoles en torno a la implicación paterna con miras a identificar su estructura y tendencias al cambio. Para ello se analizan ocho grupos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
0
9
0
2
Order By: Relevance
“…College educated fathers contribute more to childcare and housework (in absolute time) than the rest of fathers in very low-fertility countries (Sullivan et al, 2014). However, other findings on the effect of education on childcare involvement are not so conclusive for the Spanish case (Barbeta-Viñas & Cano, 2017; Fernández-Cornejo et al, 2016; Romero-Balsas, 2015). Again, it cannot be concluded that highly educated fathers share routine childcare in a more egalitarian way, even if their contribution is higher in absolute terms.…”
Section: Factors That Promote Involved Fatherhood and Shared Childcarementioning
confidence: 82%
See 2 more Smart Citations
“…College educated fathers contribute more to childcare and housework (in absolute time) than the rest of fathers in very low-fertility countries (Sullivan et al, 2014). However, other findings on the effect of education on childcare involvement are not so conclusive for the Spanish case (Barbeta-Viñas & Cano, 2017; Fernández-Cornejo et al, 2016; Romero-Balsas, 2015). Again, it cannot be concluded that highly educated fathers share routine childcare in a more egalitarian way, even if their contribution is higher in absolute terms.…”
Section: Factors That Promote Involved Fatherhood and Shared Childcarementioning
confidence: 82%
“…Socioeconomic status consists of educational attainment and occupational status, which are considered key determinants for parental involvement (Barbeta-Viñas & Cano, 2017). Educational attainment is widely recognized as being positively associated with more egalitarian gender attitudes (Barbeta-Viñas & Cano, 2017).…”
Section: Factors That Promote Involved Fatherhood and Shared Childcarementioning
confidence: 99%
See 1 more Smart Citation
“…This shift has been attributed to increasing maternal labor force participation and the spread of gender egalitarian and intensive parenting ideologies (Esping-Andersen, 2009). In this emerging model of involved fatherhood, fathers are not only expected to act as income providers but also to actively engage with the day-to-day caring and upbringing of their children (Barbeta & Cano, 2017).…”
mentioning
confidence: 99%
“…Em um contexto ideal, eles deveriam atuar como os principais provedores de mecanismos de proteção, satisfazendo as necessidades da criança em termos de carinho, cuidados e estabilidade, fatores que compõem uma parentalidade positiva (Linhares, 2015;Pereira, Goes, & Barros, 2015). As interações entre pais e filhos, caracterizadas por envolvimento parental, vêm sendo amplamente estudados, especialmente a relação pai-filho, tendo em vista a modificação da participação deste nas últimas décadas em relação ao cuidado infantil (Barbeta & Cano, 2017;Lamb, Pleck, Charnov, & Levine, 1985;Schmidt et al, 2019).…”
unclassified